THE LEGAL SANCTIONS APPLICATION FOR BUSINESS ACTORS AGAINST ILLEGAL COSMETICS CIRCULATION - Savira, Aulia Putri; Karim, Karim (jfpublisher, 2022)
Along with the development of science and technology from time to time, human needs are also growing. Not only the need for housing, clothing, food, health and education. The need to beautify itself is now a top priority in supporting daily appearance. Nowadays, it is found that many consumers buy cosmetic products that do not have quality, and there are no cosmetic products registered or not in BPOM. The low price offered comes from materials purchased with quality which is not good or even dangerous and does not use marketing authorization. The purpose of this research is to find out and understand how business actors are responsible for consumers who use illegal cosmetic products and are made from dangerous ingredients. The type of research used in this research is normative, by examining the application of the rules or norms in positive law which is then related to the problems in this research. Consumers have the right to get comfort, security, and safety in using the cosmetic products offered to them. Based on Article 19 of Law No. 8/1999 concerning Consumer Protection. This research analyses a problem which the problems include, first, how is the legal protection for consumers against the circulation of illegal cosmetics and the second is how the form of accountability for business actors who market and issue cosmetic products illegally.